Fiscal Consolidation: Part 1. How Much is Needed and How to Reduce Debt to a Prudent Level? - Sutherland, Douglas (OECD Economics Department Working Papers, 2012)
The economic and financial crisis was the catalyst for a fiscal crisis that engulfs many OECD countries. In most countries, budget deficits soared as a result of the economic slump, weaker revenues and the policy response to the crisis. Consolidating the public finances is an important challenge for many countries. Estimates of fiscal gaps suggest that substantial and sustained fiscal tightening will be needed in nearly all countries to bring debt down to prudent levels. However, given a weak global economy, implementing a large fiscal tightening could be particularly costly. Structuring consolidation packages to use instruments with low multipliers initially and enhancing the institutional framework for fiscal policy to lend greater credibility to the commitment to consolidate over time may help minimise the trade-offs with growth in the short run. In most countries there is scope to target spending programmes more effectively and eliminate distortions in taxation and re-orientate taxation to minimise distortions. Such measures, buttressed by structural reforms, such as to unsustainable pension systems, can underpin fiscal sustainability, while minimising the costs to long-run growth